Assessment of Intra-Fraction Mediastinal and Hilar Lymph Node Movement and Comparison to Lung Tumor Motion Using Four-Dimensional CT - Donnelly, Eric D. (2007)
PURPOSE: To quantify the amount of free-breathing motion measured using 4D CT scans of mediastinal and hilar lymph nodes and to compare this motion to the primary lung tumor motion. METHODS: Twenty patients, with prior 4D CT scans, having primary lung cancer and radiographically positive lymph nodes were retrospectively analyzed. The 4D CT data sets were divided into four respiratory phases and the primary tumor and radiographically positive nodes were contoured. Geometric and volumetric analysis was performed to analyze the motion of the primary tumors and the lymph nodes. RESULTS: The mean lymph node motion was 2.6 mm in the medio-lateral direction and 2.5 mm in the antero-posterior direction and 5.2 mm in the cranio-caudal direction with a maximum of 14.4 mm. All lymph nodes were found to move inferiorly during inspiration, with 12.5% of nodes moving more than 1 cm. Lymph nodes located below the carina showed significantly more motion than those above the carina (P = 0.01). In comparing the primary tumor motion to the lymph node motion, no correlation was identified. CONCLUSIONS: 4D CT scans can be used to measure the motion for the primary lung tumor and pathologic lymph nodes encountered during the respiratory cycle. Both the primary lung tumor and the lymph node need to be examined to assess their individual degree of motion. The study demonstrated the need for individualized plans to assess the heterogeneous motion encountered in both primary lung tumors and among lymph node stations.